Evaluation of the prevalence, prenatal risk factors & clinical profiles of Paediatric Patients with congenital heart disease - Ansari, Iqbal Mohammed; Ambhore, Jaishree (Indian Journal of Child Health, 2025)
Introduction: Congenital Heart Diseases (CHD’s) are amongst the major congenital malformations contributing to infant mortality. Most CHDs are diagnosed in infancy. Later, in childhood or adolescence, CHD patients may present differently. Objectives: To evaluate the prevalence, maternal risk factors and clinical profile of all children with CHD at a tertiary care centre in Bhopal. Materials and Methods: This prospective, observational study was conducted at a tertiary care centre in Bhopal from Feb 2018 to Feb 2020. Approval from the ethical committee was obtained prior to the commencement of the study. Children up to 13 years of age, admitted with the features of CHD for the first time in out institution, were included in this study. A detailed history and clinical examination were carried out and a diagnosis of CHD was confirmed with 2D Echocardiography. Results: A total of 224 patients were admitted with the features of CHD for the first time during the study period. In our study, the commonest lesion was VSD (29.01%) followed by ASD (14.73%), PDA (12.5%), and TOF (9.37%). Among the clinical presentation, fast breathing (90.17%) was the most common symptom. Conclusion: In our study, VSD was found to be the most common acynaotic CHD and TOF was the most common cynotic CHD. The most common presenting feature was breathing difficulty. In order to improve prenatal detection of CHD’s, it is imperative to have a deep understanding of maternal risk factors.